Peningkatan Hasil Belajar Peserta Didik Dengan Menggunakan Media Audio Visual Pada Mata Pelajaran PPKn Di Kelas 1 SD Negeri 6 Cakranegara Tahun Pelajaran 2022/2023 - Safinatun Najat; Sri Herawati; Siti Rohana Hariana Intiana; Rizki Lolina Shaumy (Fakultas Keguruan dan Ilmu Pendidikan Universitas Samawa, 2023)
This study aims to improve the learning outcomes of Pancasila and Civic Education students using audio-visual media. This research was conducted in grade 1 of SD Negeri 6 Cakranegara which amounted to 34 students, consisting of 12 boys and 22 girls. This research process consists of precycle, cycle I and cycle II. The research techniques used are tests and observation sheets. The results of this study show that the use of audio-visual learning media can improve learning outcomes. The improvement can be seen from the quality of learning, the activeness of students, the enthusiasm and enthusiasm of students and the learning outcomes obtained. At the time of pre-cycle, it is known that the average value of students is 67 which is still below KKM 75, so it needs to be improved. So in cycle I showed the average score of students 80 and increased to 88 in cycle II. The percentage of completion of the precycle, cycle I and cycle II respectively 47.06% increased to 64.71% and continued to increase to 88.24%. Based on the results of this study, it is known that the use of audio-visual learning media can improve student learning outcomes.